2023
DOI: 10.1186/s12889-023-15043-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in knowledge, attitudes, and practices with respect to type 1 diabetes among Saudi public-school teachers

Abstract: Background Children with type 1 diabetes mellitus (T1DM) need carefully monitoring even during school hours to avoid emergencies. Hence, it is crucial for teachers to have appropriate knowledge and positive attitudes toward diabetes to effectively manage the disease and its complications. This study aimed to compare the knowledge, attitudes, and practices with respect to T1DM among Saudi male and female public-school teachers living in Jeddah and to identify the associated factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We also found that females benefited more from CHM treatment than males. An expanding body of evidence on gender differences shows that, in general, females have more health-related knowledge and exhibit more healthy behaviors than males [ 16 , 17 ]. In this case, females may be more willing to conform to the prescribed medical regimen, which in turn lessens the subsequent risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that females benefited more from CHM treatment than males. An expanding body of evidence on gender differences shows that, in general, females have more health-related knowledge and exhibit more healthy behaviors than males [ 16 , 17 ]. In this case, females may be more willing to conform to the prescribed medical regimen, which in turn lessens the subsequent risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous surveys focusing on gender differences in health-related knowledge and healthy behaviors found that females are more aware of the importance of self-care than males. 24 , 25 In this case, females may be more attuned to adhering to the prescribed medical regimen to minimize the likelihood of sarcopenia. Additionally, the release of sex hormones, especially estrogen, may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%